A Development of Hot and Cold Drink Flavor Stock Inventory System - Adnan, Najwa (Applied Information Technology And Computer Science, 2023)
Hot and cold coffee consumption remains a daily ritual for Malaysian. Bareezta Coffee is a small company that sells hot and cold drink flavour which only uses a manual system to manage the stock. Current system used is manually system that lack of security, ineffective stock control and not provide a report. The main objective of this project is to develop a computerized inventory system that manage the stock automatically. The methodology that been selected is prototyping because the developing process need a lot of user feedback. Using prototyping will increase the chances of top-quality product being produced and the chance of failure is low. After the development completed, the objective of this project has been achieved which is provide 8 module function with a better security, product management, stock control and provide an accurate data. In brief, the project allows the users to easily manage the business product and stock.